The Relationship between Severity of Anemia and Nutritional Factors Determinant at Primary Health Care Centers in Baghdad City - Eman Abdul- Hamza AL-Khafajy1 , Rabea Mohsen Ali2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: To determine the relationship between severity of anemia and nutritional factors determinantat Primary Health Care Centers. Methods: A descriptive study has been carried out at AL.Russafa HealthDirectorate (Bab AL Muadham, and AL Mustanseria) ideal training health care center. AL-Karkh HealthDirectorate ( AL-Salam) ideal training health care center. Non-probability sample consists of (76) anemicpregnant women. questionnaire has been designed and constructed to be used as a means of data collection.Data collection is performed through interview techniques, and the use of the study instrument afterpermission were obtained from the pregnant women for the period 2nd January to 17th March 2020. Results:The results of nutritional factors indicates that (consumption of dairy products, vegetables, eggs, and fruits)are highly consumed per day (77.6%, 100%, 46.1%, and 92.1%) as indicated by high mean scores. While(consumption of poultry meat, dates and nuts) are moderately consumed per weeks (55.3%, and 56.6%).The remaining nutritional items are lower consuming that is (red meat products, fish, liver, and nutritionalplants). Sever anemia found in (6.6%), moderate severity of anemia in (61.8%), and mild anemia in ( 31.6%).high significant relationships found among severity of anemia with consumption of red meat, consumptionof poultry meat, and fish consumption (p-value= 0.004, 0.001, and 0.005); the finding also show significantrelationship between severity of anemia and eating nutritional plants (p-value=0.007). Conclusions: thestudy results concluded high significant relationships between severity of anemia with consumption of redmeat, consumption of poultry meat, and fish consumption and eating nutritional plants. Recommendation:Teach women in pregnancy age to dietary habits as a part of an overall approach to health promotion,Increasing level of awareness in women and their families about the risk of anemia on pregnancy.